2020
DOI: 10.1071/fp20010
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of crop load on nitrogen uptake and reserve mobilisation in Vitis vinifera

Abstract: Nitrogen deficit affects both crop production and composition, particularly in crops requiring an optimal fruit N content for aroma development. The adaptation of cultural practices to improve N use efficiency (NUE) (i.e. N uptake, assimilation and partitioning) is a priority for the sustainable production of high-quality crops. A trial was set on potted grapevines (Vitis vinifera L. cv. Chasselas) to investigate the potential of crop limitation (via bunch thinning) to control plant NUE and ultimately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Grape δ 15 N values are usually less than soil δ 15 N values (Durante et al, 2016). After grapevine N assimilation, a 15 N enrichment can be observed from roots (6.6 mUr on average) to must (33.7 mUr on average) (Verdenal et al, 2020). N fractionation is related to several factors, such as water availability and fruit load.…”
Section: N Isotope Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grape δ 15 N values are usually less than soil δ 15 N values (Durante et al, 2016). After grapevine N assimilation, a 15 N enrichment can be observed from roots (6.6 mUr on average) to must (33.7 mUr on average) (Verdenal et al, 2020). N fractionation is related to several factors, such as water availability and fruit load.…”
Section: N Isotope Compositionmentioning
confidence: 99%
“…The water constraint that a grapevine can face during the vegetative season will negatively influence wine δ 15 N values (Spangenberg and Zufferey, 2018). Conversely, fruit load will positively influence must δ 15 N values; i.e., from 19.5 mUr on average under low-yielding conditions to 33.7 mUr under high-yielding conditions (Verdenal et al, 2020).…”
Section: N Isotope Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, the differences in productivity and cluster size between both varieties can affect the uptake and accumulation of nutrients in the blades in veraison. Recently, Verdenal et al [47] reported that fertilizer N uptake and its assimilation in Chasselas (Vitis vinifera) grapevines appeared to be strongly stimulated by high-yielding conditions. Interestingly, grapevines were able to modulate root N reserve mobilization and fertilizer N uptake in function of the crop load, thus maintaining a uniform N concentration in fruits [47].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Verdenal et al [47] reported that fertilizer N uptake and its assimilation in Chasselas (Vitis vinifera) grapevines appeared to be strongly stimulated by high-yielding conditions. Interestingly, grapevines were able to modulate root N reserve mobilization and fertilizer N uptake in function of the crop load, thus maintaining a uniform N concentration in fruits [47]. K/Mg ratio is an important factor in determining Mg uptake and high K/Mg ratio determines low Mg uptake [48].…”
Section: Discussionmentioning
confidence: 99%